The Effects of Age, Biological Maturation and Sex on the Development of Executive Functions in Adolescents - Laureys, Felien; Middelbos, Lotte; Rommers, Nikki; De Waelle, Silke; Coppens, Eline; Mostaert, Mireille; Deconinck, Frederik J. A.; Lenoir, Matthieu (Frontiers in Physiology, 2021)
The development of executive functions (EF) has been widely investigated and is associated with various domains of expertise, such as academic achievement and sports performance. Multiple factors are assumed to influence the development of EF, among them biological maturation. Currently the effect of biological maturation on EF performance is largely unexplored, in contrast to other domains like physical development or sports performance. Therefore, this study aimed (a) to explore the effect of chronological age on EF performance and (b) to investigate to what extent age-related changes found in EF are affected by biological maturation on both sexes. To this end, EF performance and degree of maturity, indexed by percentage of predicted adult height (%PAH), of 90 adolescents (11–16 years old, 54% males) were measured on three occasions in a time frame of 12 months. A Generalized Estimating Equation (GEE) approach was used to examine the association between chronological age and %PAH and the weighted sum scores for each EF component (i.e., inhibition, planning, working memory, shifting). All models were run separately for both sexes. The males’ results indicated that EF performance improved with age and degree of maturity on all four components. Interaction effects between age and %PAH on inhibition showed that at a younger age, males with a higher %PAH had a lower chance of performing well on inhibition, whereas at later ages, males with a higher %PAH had a higher chance to have a good inhibition performance. For working memory, it seems that there is no maturity effect at a younger age, while at later ages, a disadvantage for later maturing peers compared to on-time and earlier maturing male adolescents emerged. Females showed slightly different results. Here, age positively influenced EF performance, whereas maturity only influenced inhibition. Interaction effects emerged for working memory only, with opposite results from the males. At younger ages, females with lower %PAH values seem to be scoring higher, whereas at later ages, no maturity effect is observed. This study is one of the first to investigate the effect of biological maturation on EF performance, and shows that distinct components of EF are influenced by maturational status, although the effects are different in both sexes. Further research is warranted to unravel the implications for maturation-driven effects on EF that might significantly affect domains of human functioning like academic achievement and social development.